Forecasting Sustainable Development of Organic Crop Production in Kazakhstan (oilseeds) - B. B. Bolatbek; M. S. Bekturganova; G. S. Satbaeva; N. A. Abilkayir (Экономика: стратегия и практика)
The purpose of this study is to analyze the state of organic crop production in Kazakhstan. In the research work, the factors affecting oilseeds of Kazakhstan were studied. The current research work is aimed at analyzing the general dynamics of organic agriculture in the republic of Kazakhstan. The period under review covered seventeen years from 2004 to 2021. To analyze the data, the r program was used and a correlation – regression analysis was carried out. The results of the study, the results of the forecast of harvesting oil-seeds for 2023-2026 for 4 years were presented. The results of the study show that the volume of organic crop production in Kazakhstan has a significant impact on the volume of gross output and arable land. Organic agriculture is the main goal of producing environmentally friendly products. The results of the study can be used at the state or local level to develop programs and strategies on the importance of ensuring the sustainable development of organic crop production in the regions of Kazakhstan, ensuring the safety of domestic oilseeds, sustainable development of the oilseeds market.